Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Plants alter their vertical root distribution rather than biomass allocation in response to changing precipitation - Bingwei Zhang; Marc W. Cadotte; Shiping Chen; Xingru Tan; Cuihai You; Tingting Ren; Minling Chen; Shanshan Wang; Weijing Li; Chengjin Chu; Lin Jiang; Yongfei Bai; et al. (Ecology, 2019)
Elucidating the variation of allocation pattern of ecosystem net primary productivity ( NPP ) and its underlying mechanisms is critically important for understanding the changes of aboveground and belowground ecosystem functions. Under optimal partitioning theory, plants should allocate more NPP to the organ that acquires the most limiting resource, and this expectation has been widely used to explain and predict NPP allocation under changing precipitation. However, confirmatory evidence for this theory has mostly come from observed spatial variation in the relationship between precipitation and NPP allocation across ecosystems, rather than directly from the influences of changing precipitation on NPP allocation within systems. We performed a 6‐yr five‐level precipitation manipulation experiment in a semiarid steppe to test whether changes in NPP allocation can be explained by the optimal partitioning theory, and how water requirement of plant community is maintained if NPP allocation is unaltered. The 30 precipitation levels (5 levels × 6 yr) were divided into dry, nominal, and wet precipitation ranges, relative to historical precipitation variation over the past six decades. We found that NPP in both aboveground ( ANPP ) and belowground ( BNPP ) increased nonlinearly as precipitation increased, while the allocation of NPP to BNPP ( f BNPP ) showed a concave quadratic relationship with precipitation. The declined f BNPP as precipitation increased in the dry range supported the optimal partitioning theory. However, in the nominal range, NPP allocation was not influenced by the changed precipitation; instead, BNPP was distributed more in the surface soil horizon (0–10 cm) as precipitation increased, and conversely more in the deeper soil layers (10–30 cm) as precipitation decreased. This response in root foraging appears to be a strategy to satisfy plant water requirements and partially explains the stable NPP allocation patterns. Overall, our results suggest that plants can adjust their vertical BNPP distribution in response to drought stress, and that only under extreme drought does the optimal partitioning theory strictly apply, highlighting the context dependency of the adaption and growth of plants under changing precipitation.

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

Comparative analysis of a panel of biomarkers related to protein phosphatase 2A between laryngeal squamous cell carcinoma tissues and adjacent normal tissues - Han-ying Wang; Hui Yuan; Jing-hui Liu; Bei-lei Wang; Kai-lun Xu; Pu Huang; Zhi-hong Lin; Li-hong Xu (Journal of Zhejiang University-SCIENCE B, 2019)

Exosomes from patients with Parkinson’s disease are pathological in mice - Chao Han; Nian Xiong; Xingfang Guo; Jinsha Huang; Kai Ma; Ling Liu; Yun Xia; Yan Shen; Jie Li; Haiyang Jiang; Luxi Wang; Shiyi Guo; et al. (Journal of Molecular Medicine, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Circular RNAs exhibit extensive intraspecific variation in maize - Zi Luo; Linqian Han; Jia Qian; Lin Li (Planta, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Cloning, in silico characterization, subcellular localization, and expression of a heat shock cognate 70 kDa protein/gene (EjHsc70-2) from Eriobotrya japonica - Shoukai Lin; Ti Wu; Ming Li; Xiaoming Huang; Yanqing Zhang; Linxiao Han; Bisha Wu; Yu Chen; Suying Lin; Dahe Lin; Minlan Wu; Jincheng Wu (Acta Physiologiae Plantarum, 2019)

Natural CAC chemopreventive agents from Ilex rotunda Thunb. - Yueqing Han; Lin Zhang; Wei Li; Xinran Liu; Jiao Xiao; Gang Chen; Ning Li (Journal of Natural Medicines, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Evaluation of the diagnostic ratios of adamantanes for identifying seriously weathered spilled oils from simulated experiment and actual oil spills - Bin Han; Li Zheng; Qian Li; Faxiang Lin; Yu Ding (Environmental Geochemistry and Health, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Paleogeomorphology restoration and the controlling effects of paleogeomorphology on karst reservoirs: a case study of an ordovician-aged section in Tahe oilfield, Tarim Basin, China - Changcheng Han; Chengyan Lin; Ting Wei; Chunmei Dong; Lihua Ren; Xianguo Zhang; Li Dong; Xu Zhao (Carbonates and Evaporites, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)